2019
DOI: 10.1136/oemed-2018-105598
|View full text |Cite
|
Sign up to set email alerts
|

Destress 9-1-1—an online mindfulness-based intervention in reducing stress among emergency medical dispatchers: a randomised controlled trial

Abstract: ObjectivesEmergency medical dispatchers (EMDs) experience significant stress in the workplace. Yet, interventions aimed at reducing work-related stress are difficult to implement due to the logistic challenges associated with the relatively unique EMD work environment. This investigation tested the efficacy of a 7-week online mindfulness-based intervention (MBI) tailored to the EMD workforce.MethodsActive-duty EMDs from the USA and Canada (n=323) were randomly assigned to an intervention or wait list control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The program methodology in most of them was intervention with personal attendance, with mindfulness practice at home, while listening to audio recordings. However, some studies used online intervention [10,11]. Table 1 shows the results of the studies selected for systematic review and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The program methodology in most of them was intervention with personal attendance, with mindfulness practice at home, while listening to audio recordings. However, some studies used online intervention [10,11]. Table 1 shows the results of the studies selected for systematic review and meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Therefore, when mindfulness-based intervention was carried out in the work-place to reduce stress and depression or to improve sleep quality, a favorable effect was observed after its completion [2]. Nevertheless, with online intervention, such as the intervention carried out by Aikens et al [10] and Lilly et al [11], heterogeneity was found to be lower. In spite of this, according to Sard-Pecka et al [31], both types of interventions (attended and online) reduce stress levels.…”
Section: Summary Of Evidencementioning
confidence: 99%
“… #730 Hospice and Palliative Care Provider Experiences with Meditation Using Mobile Applications Lehto et al 2018 Oncology Nursing Forum USA To evaluate perceived benefits, challenges, and recommendations following participation in a workplace mobile application– and email-based meditation research program. #871 Destress 9–1-1—an online mindfulness-based intervention in reducing stress among emergency medical dispatchers: a randomized controlled trial Lilly et al 2019 Occupational and Environmental Medicine USA/CAN This investigation tested the efficacy of a 7-week online mindfulness-based intervention (MBI) tailored to the EMD workforce. #1437 The use of online MBSR audio in medical staff during the COVID-19 in China Liu et al 2020 European Review for Medical and Pharmacological Sciences China This study aims to survey medical staff’s acceptance of online Mindfulness-Based Stress Reduction (MBSR) during the Novel Coronavirus Pneumonia (NCP), and to know some information of physical and emotional response of those medical staff who worked at the forefront of COVID-19, through the playback amount of the online MBSR training.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Existing literature suggests that MBIs, especially mindfulness-based stress reduction (MBSR) interventions, are effective in reducing anxiety, depression, and stress. [15][16][17][18][19] Previous studies suggest preliminary efficacy of MBSR among PLWH in terms of behavioral, psychosocial, and clinical outcomes, including psychological well-being, ART side effects, HIV-related chronic pain, and T-cell activity. [20][21][22][23][24] MBSR could be an appropriate approach for stress reduction among PLWH given that they are cost-effective treatments with little or no adverse effects.…”
Section: Introductionmentioning
confidence: 99%